IMPROVING PERFORMANCE THROUGH VARIATION OF WORK EXPERIENCE AND TRAINING QUALITY IN THE COOPERATION OF SAVE LOAN AND FINANCING SYARIAH (KSPPS BMT) IN SEMARANG REGENCY AND SEMARANG CITY - Muhari Muhari; Moch Zulfa (IJIBE (International Journal of Islamic Business Ethics), 2017)
This research aims to figure out the effect of social competence, variation of work experience, and quality of training on HR performance with information technology as intervening. The sample of this research consist of 71 respondents from Semarang regency and Semarang city. Regression analysis was performed with the software Statistical Package for Social Science (SPSS). The results of the analysis showed that the social competencies can improve HR performance through the variation of work experience and the quality of training that moderate information technology.The empirical findings indicate that Social Competence, variation of work experience, and quality Training have significant effect on HR performance. Information technology is not able to moderate the effect of experience variation on HR performance and information technology is also not able to moderate the effect of the quality of training on HR performance.Keywords : Social competence, information technology, variation of experience, Quality Training, performance.